Titular Bishops in the Law of the Latin Church - Wroceński, Józef (Prawo Kanoniczne, 2021)
TheauthorinhisstudyanalysedthelegalpositionoftitularbishopsintheLatinChurch. His analysisofhistoricallegaltextsledtotheconclusionthatfromthebeginningof the appearance of the titularbishops there wasagreatcontroversyaroundtheir legal statusandtasks.Theystemmedfromthechurch'sassumptionandpreviouspracticethateachdioceseshouldhaveonlyonebishop.Sotheyhadjurisdictioninabandoneddiocesesthattheycouldnotexerciseinthediocesestheycameto.Theywereappointedtodiocesestheyhadleftwiththehopeofreturningtothem.However,theirhelpfulnessandsometimes necessityinthenewdiocesesalsoproved to befunctional.Hencethepracticeofappointingcoadjutorbishopsandauxiliarybishops,nonethelesstheirpositionwasstillundervalued.Theirapprizementtookplacewithintheframeworkof the doctrine oftheSecondVaticanCouncilonthesacramentality of theepiscopalconsecrationandthecollegialityofbishops.TheCouncilgrantedallbishopsfundamentalequalityintheChurch.ItmanifestsitselfprimarilyintherighttoparticipateintheGeneralCouncil,theSynodofBishops, andintheworkoftheRomanCuria.TheirpositioninthelocalChurchhasalsochanged.TheprovisionsofthenewCodesignificantly added value to the legal position of the titularbishops, but did not make a radical change that would close the discussion on the role and tasks of titular bishopsintheChurch.